2005
DOI: 10.1128/jb.187.2.639-648.2005
|View full text |Cite
|
Sign up to set email alerts
|

TheErwinia chrysanthemiType III Secretion System Is Required for Multicellular Behavior

Abstract: Enterobacterial animal pathogens exhibit aggregative multicellular behavior, which is manifested as pellicles on the culture surface and biofilms at the surface-liquid-air interface. Pellicle formation behavior requires production of extracellular polysaccharide, cellulose, and protein filaments, known as curli. Protein filaments analogous to curli are formed by many protein secretion systems, including the type III secretion system (TTSS). Here, we demonstrate that Erwinia chrysanthemi, which does not carry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
140
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(148 citation statements)
references
References 51 publications
6
140
2
Order By: Relevance
“…Pellicle formation in 3937 requires a functional type III secretion system (T3SS) (23). A similar phenomenon has been observed in Escherichia coli, where a degenerate T3SS is required for both virulence and bacterial aggregation (10).…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…Pellicle formation in 3937 requires a functional type III secretion system (T3SS) (23). A similar phenomenon has been observed in Escherichia coli, where a degenerate T3SS is required for both virulence and bacterial aggregation (10).…”
mentioning
confidence: 80%
“…The EC16 HrpN produced in King's B medium was sensitive to proteinase K, further evidence that the EC16 protein is localized to the outside of the bacterial cell and that localization of HrpN to the outside of the bacterial cell is not sufficient for aggregation (data not shown). Similarly, we have found that strain 3937 produces HrpN at 36°C even though no pellicle forms at this temperature (23).…”
mentioning
confidence: 87%
See 3 more Smart Citations